Potential Role of Sequential Solid-State and Submerged-Liquid Fermentations in a Circular Bioeconomy - José Pablo López-Gómez; Joachim Venus (Fermentation, 2021)
An efficient processing of organic solid residues will be pivotal in the development of the circular bioeconomy. Due to their composition, such residues comprise a great biochemical conversion potential through fermentations. Generally, the carbohydrates and proteins present in the organic wastes cannot be directly metabolized by microorganisms. Thus, before fermentation, enzymes are used in a hydrolysis step to release digestible sugars and nitrogen. Although enzymes can be efficiently produced from organic solid residues in solid-state fermentations (SsF), challenges in the development and scale-up of SsF technologies, especially bioreactors, have hindered a wider application of such systems. Therefore, most of the commercial enzymes are produced in submerged-liquid fermentations (SmF) from expensive simple sugars. Instead of independently evaluating SsF and SmF, the review covers the option of combining them in a sequential process in which, enzymes are firstly produced in SsF and then used for hydrolysis, yielding a suitable medium for SmF. The article reviews experimental work that has demonstrated the feasibility of the process and underlines the benefits that such combination has. Finally, a discussion is included which highlights that, unlike typically perceived, SsF should not be considered a counterpart of SmF but, in contrast, the main advantages of each type of fermentation are accentuated in a synergistic sequential SsF-SmF.